2018
DOI: 10.1111/ahe.12412
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of embalming fluids on the structures and properties of tissue in human cadavers

Abstract: Cadaveric material has long been used to teach anatomy and more recently to train students in clinical skills. The aim of this study was to develop a systematic approach to compare the impact of four embalming solutions on the tissues of human cadavers. To this end, a formalin‐based solution, Thiel, Genelyn and Imperial College London soft‐preservation (ICL‐SP) solution were compared. The effect of these chemicals on the properties of the tissue was assessed by measuring the range of motion (ROM) of joints and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 25 publications
0
36
0
4
Order By: Relevance
“…There is a paucity of literature directly comparing the quality of tissues resulting from different embalming methods to date. In a recent series of studies, a group from the University of Dundee, Scotland, compared student (Balta et al, 2015b) and staff perceptions (Balta et al, 2017), tissue haptic properties (Kennel et al, 2018; Balta et al, 2019a), and antimicrobial properties (Balta et al, 2019b) of formaldehyde and Thiel‐based embalming techniques. They found that Thiel embalming made undergraduate students feel more uncomfortable than formaldehyde‐fixed tissues as they looked more lifelike (Balta et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of literature directly comparing the quality of tissues resulting from different embalming methods to date. In a recent series of studies, a group from the University of Dundee, Scotland, compared student (Balta et al, 2015b) and staff perceptions (Balta et al, 2017), tissue haptic properties (Kennel et al, 2018; Balta et al, 2019a), and antimicrobial properties (Balta et al, 2019b) of formaldehyde and Thiel‐based embalming techniques. They found that Thiel embalming made undergraduate students feel more uncomfortable than formaldehyde‐fixed tissues as they looked more lifelike (Balta et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the tissues provided for undergraduate education, it has been shown to be advantageous to introduce a level of artificiality concerning tissue color and stiffness (Balta et al, 2015b; Hammer et al, 2015b). While formaldehyde fixation results in stiffer, unpliable tissues with a bleached appearance, other techniques such as light embalming (Messmer et al, 2010) or Thiel embalming (Thiel, 1992; Benkhadra et al, 2009; Jaung et al, 2011; Balta et al, 2015a; Hammer et al, 2015b; Balta et al, 2019a) result in colorfast and elastic tissues with particular suitability for postgraduate education and specialist workshops. The deliquescent tissue behavior of Thiel embalming is extremely helpful for (simulated) surgical interventions, which require a realistic range of tissue mobility (Groscurth et al, 2001; Eisma et al, 2011; Jaung et al, 2011; Eisma et al, 2013; Hammer et al, 2015a,b; Tomlinson et al, 2016; Balta et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of formalin preservation and histological process could have influenced the tissue relationships and dimensions. Although formalin retained shape and size of organs and vessels, Genelyn and Imperial College London soft-preservation (ICL-SP) solution technique may faithfully mimic cadavers' joints compared to un-embalmed cadavers [22]. Thus, future studies should compare our findings using different embalming solutions on the human cadavers' tissues.…”
Section: Discussionmentioning
confidence: 93%
“…These practices were very numerous and embalmer‐dependent, which is still the case nowadays (Brenner, ; Hambly, ; Balta et al. ). From this important cultural diversity, a huge variability in embalming fluids has been noticed.…”
Section: Introductionmentioning
confidence: 99%
“…Embalming practices have been known since antiquity, and were developed mainly for religious reasons (Ancient Egypt culture, for example). These practices were very numerous and embalmer-dependent, which is still the case nowadays (Brenner, 2014;Hambly, 2016;Balta et al 2019). From this important cultural diversity, a huge variability in embalming fluids has been noticed.…”
Section: Introductionmentioning
confidence: 99%